2006
DOI: 10.1080/14767050500381123
|View full text |Cite
|
Sign up to set email alerts
|

DEFB-1 genetic polymorphism screening in HIV-1 positive pregnant women and their children

Abstract: Our results evidence a high frequency of the -44 CC allele in HIV-1 infected mothers and their children with augmented potential risk of maternal fetal transmission. This potential vertical transmission risk has been successfully prevented by antiretroviral drug treatment and cesarian section of the HIV-1 positive mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 8 publications
2
24
1
Order By: Relevance
“…It is thought to be constitutively expressed in the vitreous, and one of the SNPs we identified, –44G→C, has been previously linked with a predisposition to infection. Two independent studies have shown an association between –44C allele and HIV infection 5 7. Furthermore, Hu et al 6 observed an increase in the –44C allele associated with patients having chronic obstructive pulmonary disease when compared with healthy smokers.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It is thought to be constitutively expressed in the vitreous, and one of the SNPs we identified, –44G→C, has been previously linked with a predisposition to infection. Two independent studies have shown an association between –44C allele and HIV infection 5 7. Furthermore, Hu et al 6 observed an increase in the –44C allele associated with patients having chronic obstructive pulmonary disease when compared with healthy smokers.…”
Section: Resultsmentioning
confidence: 98%
“…We present a case of bilateral endophthalmitis and show the carriage of the –44CC genotype in β-defensin 1. The polymorphism has previously been linked to increased susceptibility to infection 47…”
mentioning
confidence: 99%
“…As is the case with other genes, some of these SNPs may influence the biological function of the antimicrobial peptides. In fact, previous studies suggest that some SNPs in DEFB1, have been associated with differential risks of HIV-1 infection [26-28]. However, HBD polymorphisms and their relationships to the expression levels at mucosal sites have not been systematically studied as potential modifiers of the risk of HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although the anti-HIV-1 role of HBD-1 has not been previously reported, an association between SNPs in DEFB1 and the risk of acquiring HIV-1 infection has been suggested (44)(45)(46)(47). In our group, studies have indicated that the A692G polymorphism is associated with resistance to HIV-1 infection among discordant couples (42).…”
Section: Discussionmentioning
confidence: 70%
“…Previous SNP studies have suggested that -44 C/G (site 668), -20 A/G (site 692) and -52 G/A (site 660) SNPs in DEFB1 are associated with differential risks of vertical transmission of HIV-1 (44)(45)(46)(47). Furthermore, the frequency of the SNP genotype A692G G/G in the DEFB1 gene was significantly higher in ESN compared to SP individuals and suggested an association of this SNP with resistance to HIV-1 infection (42).…”
mentioning
confidence: 99%